Review of The Music Improvisation Company 1968-1971, Tony Oxley: February Papers, Evan Parker: Saxophone Solos, Duo: Derek Bailey, Tristan Honsinger, Barry Guy: Statements V-XI for Double Bass and Violone, Company 3, Company 4, and Company 5 - Potter, Keith (Contact: A Journal for Contemporary Music (1971-1990), 1978)